FAKTOR FAKTOR YANG MEMPENGARUHI RETURN ON ASSET DALAM MENGUKUR KINERJA KEUANGAN PERBANKAN - Wahyu Murti (Fakultas Ekonomi Universitas Borobudur, 2014)
Simultaneously Capital Adequecy Ratio ( CAR ) and Net Profit Margin ( NPM ) sigpificantl influence the Return on Assets ( ROA ) with the acquisition ( R - square = 0.750 ) Th: condition is also able to explain the Capital Adequecy Ratio ( CAR ) and Net Profit Margin ( NPM ) , simultaneously contributing to the Return on Assets ( ROA ) this explained by the effect of 75 % , and the rest or 25% is as explaned residual esti influenced by other variables outside the model . Partially Capital Adequecy Ratio ( CAR ) has significan positive impact on Return on Asscts ( ROA ) , with the acquisition ( R - square = 0.0713) . This condition is also able to explain the Capital Adequecy Ratio ( CAR ) partially contributed to the Return on Assets ( ROA ) with the effect of 71,3 % . Partially Net Profit Margin ( NPM ) has significan positive effect on Return on Assets ( ROA ) , it is shown by the aequisition ( R - square = 0.749 ) . This condition is also able to explain , that the Net Profit Margin ( NPM ) partially contributed to the Return on Assets ( ROA ) with the effect by 74,9 % . Kata Kunci : Net Profit Margin ( NPM ),Capital Adequacy Ratio ( CAR)